Study Antibacterial Activity of Pyocyanin Extracted from Pseudomonas Aeruginosa - Rusul Idan Mohsin (Journal of Science in Medicine and Life, 2025)
The study aimed to detect Pseudomonas aeruginosa pyocyanin genes and evaluate the antibacterial activity of pyocyanin produced by P. aeruginosa isolated from burn infections. A total of 224 specimens were collected from burn patients. Culture traits, biochemical testing, and Vitek-2 system confirmation were used to make the identification. P. aeruginosa was identified in 109 (48.6%) of bacterial isolates, 30 (27.5 %) produced pyocyanin, 45 (41.3 %) produced other pigments and 34 (31.2 %) not produced any pigments. Genetically, study included used PCR technique to investigation predominance of pyocyanin pigment production genes, exhibited higher. Chloroform was used to extract pyocyanin from P. aeruginosa, and FTIR was used to identify it. The extract of pyocyanin showed broad-spectrum antibacterial activity, with the greatest activity against Gram negative. It had little effect on Staphylococcus aureus and P. fluorescens and but shown significant antibacterial efficacy against Proteus mirabilis followed by Acinetobacter baumanni, Escherichia coli and Klebsiella pneumonia.